Full modeling of high-intensity focused ultrasound and thermal heating in the kidney using realistic patient models - Suomi, V; Jaros, J; Treeby, B; Cleveland, R (Institute of Electrical and Electronics Engineers, 2018)
OBJECTIVE:High-intensity focused ultrasound (HIFU) therapy can be used for noninvasive treatment of kidney (renal) cancer, but the clinical outcomes have been variable. In this study, the efficacy of renal HIFU therapy was studied using a nonlinear acoustic and thermal simulations in three patients. METHODS:The acoustic simulations were conducted with and without refraction in order to investigate its effect on the shape, size, and pressure distribution at the focus. The values for the attenuation, sound speed, perfusion, and thermal conductivity of the kidney were varied over the reported ranges to determine the effect of variability on heating. Furthermore, the phase aberration was studied in order to quantify the underlying phase shifts using a second order polynomial function. RESULTS:The ultrasound field intensity was found to drop on average 11.1 dB with refraction and 6.4 dB without refraction. Reflection at tissue interfaces was found to result in a loss less than 0.1 dB. Focal point splitting due to refraction significantly reduced the heating efficacy. Perfusion did not have a large effect on heating during short sonication durations. Small changes in temperature were seen with varying attenuation and thermal conductivity, but no visible changes were present with sound speed variations. The aberration study revealed an underlying trend in the spatial distribution of the phase shifts. CONCLUSION:The results show that the efficacy of HIFU therapy in the kidney could be improved with aberration correction. SIGNIFICANCE:A method is proposed by that patient specific pre-treatment calculations could be used to overcome the aberration and therefore make ultrasound treatment possible.